The Influence of Brand Image And Product Features on Purchase Intention: Evidence from Biznet Internet Services in Bandung, Indonesia - Gallang Perdhana Dalimunthe; Hasbian Fauzy Perdhana (Riviera Publishing, 2026)
The Indonesian fixed broadband market has grown substantially, yet Biznet despite holding the highest download and upload speeds among major providers commands only 1.52% market share, the smallest in the sector. This paradox raises important questions about the role of non-technical factors, specifically brand image and product features, in shaping consumer purchase intention. The present study examines the partial and comparative influence of these two variables on purchase intention among active Biznet subscribers in Bandung, Indonesia. A quantitative associative research design with a causal framework was employed, with data collected from 385 respondents via structured questionnaire using purposive sampling. Instrument reliability and validity were confirmed through Cronbach's Alpha (? ? 0.847) and Pearson's Product Moment Correlation (r > 0.100) respectively. Classical regression assumptions normality, multicollinearity, and heteroscedasticity were verified prior to analysis. Multiple linear regression analysis revealed that brand image (? = 0.401; t = 7.103; p < 0.001) and product features (? = 0.397; t = 7.057; p < 0.001) both exert statistically significant positive influences on purchase intention, collectively explaining 52.4% of its variance (R² = 0.524; Adjusted R² = 0.521). Brand image emerged as the marginally dominant predictor. Descriptively, while consumers rate Biznet's connection speed most favorably (mean = 4.12), brand memorability (mean = 3.54) and value for money (mean = 3.58) remain comparatively weak, and preferential purchase intention registers in the